The role of academic achievement growth in school track recommendations - Caro, D; Lenkeit, J; Lehmann, R; Schwippert, K (2009)
Students in Germany are tracked into different forms of secondary schooling based on teachers' recommendations. The literature shows that school tracking is largely affected by academic achievement levels, but neglects the influence of individual achievement growth. The authors used data from the Berlin study ELEMENT (N = 2242) to characterize math growth trajectories, obtain reliability-adjusted measures of individual growth, and evaluate their effect on teacher's recommendations. The findings suggest that teachers reward math growth while issuing track recommendations. Females, immigrants, and higher SES students are more likely to obtain a college track recommendation other things being equal. And, the probability of a college track recommendation decreases in classes with higher achievement levels and smaller proportion of immigrants. © 2009 Elsevier Ltd. All rights reserved.